COMPARISON OF EFFICACY OF STEROIDS ALONE AND COMBINATION OF STEROIDS WITH HYALURONIDASE ON MOUTH OPENING IN ORAL SUBMUCOUS FIBROSIS PATIENTS - Liaqat , Sehrish; Ullah, Ahsan; Waqas, Muhammad Abi; Pervez, Namal; Uddin, Shahab; Ara, Nighat (Journal of Ayub Medical College Abbottabad, 2022)
Background: Eventually Oral submucous fibrosis causes pronounced stiffness and failure to open the mouth. Objectives are to determine compare the efficacy of intralesional steroids alone and combination of steroids with hyaluronidase on mouth opening in oral submucous fibrosis. Methods: It was a prospective comparative cohort study. Total of 74 patients both male and female having history of pan chewing and limited mouth opening and burning sensations were included in the study. Informed consent was taken and divided into two groups. Patients of group 1 were managed with mixture of betamethasone 1 ml and hyaluronidase 1500 IU and patients of group 2 were treated with only steroid injection of betamethasone 1 ml given intralesional, both injections were given intralesional, by multiple puncture technique and once a week and continued for twelve weeks (3 months). And data compiled and analyzed in SPSS-20. Results: The mean age of group 1 was 40.027±6.97years, and mean age of Group 2 was 37.351±5.48 years. In both groups, the greatest number of cases aged from 31-59 years. Compared to females in both groups, the majority of patients were males. In 32 (86.4)% patients of group 1 showed efficacy compared with 18[43.2] patients in group 2 [p-0.000]. Conclusion: In this study Intralesional steroids with hyaluronidase injections are more efficient for opening the mouth in patients with oral sub-mucus fibrosis.